Pengaruh Kepemilikan Asing Dan Kepemilikan Domestik Terhadap Nilai Perusahaan Melalui Modal Intelektual Sebagai Variabel Intervening - Azzahra, Tika Nur (Faculty of Economics and Business | Universitas Diponegoro, 2024)
Islamic banking is a growing financial sector that has an important role in the economy as a provider of financial services and as an investment for shareholders. This study aims to determine the effect of foreign ownership and domestic ownership on firm value through intellectual capital as an intervening variable. The population in this study are Islamic banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. Sampling using purposive sampling method with the criteria of Islamic banking companies and other provisions. Secondary data in the form of financial statements and annual reports from each company. The results of this study indicate that (1) foreign ownership has a significant effect on firm value, (2) domestic ownership has an insignificant effect on firm value, (3) foreign ownership has an insignificant effect on intellectual capital, (4) domestic ownership has an insignificant effect on intellectual capital, (5) intellectual capital has a significant effect on firm value, and (6) intellectual capital is not able to mediate the relationship between foreign ownership and domestic ownership on firm value. Future research needs to add new variables so that the results become more comprehensive.